Exergy as a useful tool for the performance assessment of aircraft gas turbine engines: A key review. (May 2016) - Şöhret, Yasin; Ekici, Selcuk; Altuntaş, Önder; Hepbasli, Arif; Karakoç, T. Hikmet
Abstract: It is known that aircraft gas turbine engines operate according to thermodynamic principles. Exergy is considered a very useful tool for assessing machines working on the basis of thermodynamics. In the current study, exergy-based assessment methodologies are initially explained in detail. A literature overview is then presented. According to the literature overview, turbofans may be described as the most investigated type of aircraft gas turbine engines. The combustion chamber is found to be the most irreversible component, and the gas turbine component needs less exergetic improvement compared to all other components of an aircraft gas turbine engine. Finally, the need for analyses of exergy, exergo-economic, exergo-environmental and exergo-sustainability for aircraft gas turbine engines is emphasized. A lack of agreement on exergy analysis paradigms and assumptions is noted by the authors. Exergy analyses of aircraft gas turbine engines, fed with conventional fuel as well as alternative fuel using advanced exergy analysis methodology to understand the interaction among components, are suggested to those interested in thermal engineering, aerospace engineering and environmental sciences.